ANALISA BEBAN PENDINGIN PRODUK PADA CONTACT PLATE FREEZER TERHADAP KINERJA KOMPRESOR DI PT. TRIMITRA MAKMUR, TARAKAN, KALIMANTAN UTARA - Samsi Samsi; Ade Hermawan; Teguh Binardi; M. Ilham; Istianto Budhi Rahardja (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Contact plate freezer (CPF) is a refrigeration machine unit to freeze products that will certainly maintain product freshness. The cooling system is running smoothly, one thing that should be noted is the cooling load on the contact plate freezer. Cooling load is the amount of heat absorbed per unit of time. Refrigeration cycle at PT. Trimitra Makmur, using a combined refrigeration cycle (multi-stage cycle), using two vapor compression cycles using two single-stage compressors. The two compressors used have the same power of 55.92 kW. As for the main components of the refrigeration system at PT. Trimitra is prosperous, among others: Compressors, condensers, expansion valves, and evaporators. The cooling load on the contact plate freezer consists of product heat load, water heat load, internal heat load, and transmission heat load. In the contact plate freezer, the load of infiltration or heat from the outside air is not calculated because at the time of production the door of the contact plate freezer is closed tightly so the value of air exchange is very small and can be ignored. In this research, it was found that the average total load on contact plate freezer 1 was 23.07079 kW, so that the average total load on all three contact plate freezers at PT. Trimitra Makmur is 69.21237 kW. From the results of data collection and calculation, the COP value in the high-stage cycle is 4.33, so the power of the high-stage compressor used is 1/4.33 of the cooling capacity of the contact plate freezer. While in the booster cycle, a COP value of 6.49 is obtained, so the booster compressor power used is equal to 1/6.49 of the cooling capacity of the contact plate freezer.